Observations on the miraxonal attraction exercised by sexually immature or adult Biomphalaria glabrata infected or not by Schistosoma mansoni - Luiz Augusto Magalhães; Eliana Maria Zanotti-Magalhães; José Ferreira de Carvalho
OBJECTIVE: The influence of age and the presence of secondary sporocysts in the miraxonal attraction exercised by Biomphalaria glabrata on miracidia of Schistosoma mansoni of the BH strain were studied. MATERIAL AND METHOD: A glass apparatus containing two compartments joined by a tube and previously tested in other experiments, was used. Specimens of B. glabrata or its snail conditioned water (SCW) selected before the first oviposition (sexually immature), after the first oviposition (adult), with or without secondary sporocysts, were used to attract the miracidia. RESULTS: It was noted that snails or their SCW containing secondary sporocysts lost the ability to attract miracidia. The sexual maturity of the snail did not influence miraxonal attraction.